WORK STRESS AND ITS IMPACT ON ADMINISTRATIVE EMPLOYEES IN A LOGISTICS SERVICE COMPANY IN GRESIK REGENCY - Safitri, Gadis Nur; Rizqi, Maulidyah Amalina (Journal of Global Business and Management Review, 2025)
This study is motivated by the increasing work pressure faced by administrative employees in logistics companies, where excessive workloads, tight deadlines, and system disruptions have become critical issues that threaten both employee well-being and operational accuracy. This study aims to analyze the causes, forms, and impacts of work stress among employees in a logistics service company in Gresik Regency. The research involved four informants consisting of the Head of HRD and three administrative employees selected through purposive sampling based on stress indicators. Using a descriptive qualitative method, data were collected through in-depth interviews and direct observation. The findings show that excessive workload, simultaneous arrival of multiple ships, multitasking beyond primary duties, system errors, and tight reporting deadlines are the main triggers of work stress. The forms of stress appear in physical fatigue, emotional tension, reduced concentration, and declining motivation. Work stress negatively affects accuracy, productivity, and employee discipline. The study concludes that improving workload management, increasing staffing, and implementing structured stress-management programs are essential to reduce work stress.